Remoção de rodamina 6G de efluentes sintéticos utilizando Clitoria fairchildiana como biossorvente de baixo custo - Silva, Andreza Miranda Barata da (Brasil, 2019)
In this work, a natural plant product Clitoria fairchildinana (CF) was used as a biosorbent to remove rhodamine 6G (R6G) from synthetic dye effluents. CF was characterized by infrared spectroscopy (FTIR), Boehm titration and measurement of zero charge point (pHPCZ). The influence of various factors, such as solution pH, contact time, adsorbent mass, and concentration of R6G has been studied by batch experiments. The optimum contact time to reach equilibrium was found to be 15 min. The optimum adsorbent dose was 8 g L-1. The maximum adsorption capacity of CF (73.84 mg g−1) was observed at pH 6.4 and 25°C. The study of adsorption kinetics and isotherms revealed that the adsorption process was better fitted by pseudo-second order and Langmuir model, respectively. The obtained thermodynamic parameters indicate that the adsorption of R6G is spontaneous and enthalpy- driven. The results show that the C. fairchildiana biosorbent can be applied as a low cost adsorbent to remove R6G from effluents, since it presented good adsorption capacity when compared to other biosorbents.